Fusi Seni Dan Teknologi Mendorong Metamorfosis Bentuk Karya Seni Rupa (Studi penciptaan karya Video Performance) - Isnanta, Satriana Didiek (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2010)
The presence of cameras,film,and video has created a synthesis between the art world's imagination with technology of mechanical reproduction. The birth of photography and cinema has brought great changes in human culture. A break in to level the concept of separation of art and technology. It is unceniable that the trend of development of contemporary art lately, so intersect at all with the development of existing technology, particulary information technology and recording media. This is evident with the emergence of several new genres in the contemporary art of Indonesia and the world.With a background as above, then the author of experimenting to make multi-media art works that exploit information technology and recording media. And this paper is the result of the experimentation process of making the work of Video Peformance. This genre according to the most interesting writers of the genres that exist in other new media art, it is associated from its long history as well as the mutation process when in contact with technological developments.Keywords : art, technology, video, performance art